Respuesta :

Answer:

These steps can be used:

  • combine -6 and 4
  • combine 15 and -3
  • multiply 2 by x and -2

Step-by-step explanation:

The equation could be solved as follows:

  2(x -6 +4) = 15 -3                 given

  2(x -2) = 15 -3                      combine -6 and 4

  2(x -2) = 12                          combine 15 and -3

  2x -4 = 12                            multiply 2 by x and -2

  2x = 16                                add 4 to both sides

  x = 8                                    divide both sides by 2

_____

Alternate solution

At step 4, you could have

  x -2 = 6                              divide both sides by 2

  x = 8                                   add 2 to both sides

ACCESS MORE